1992
DOI: 10.1103/physrevb.45.2537
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg model of subdomain fcc clusters: A Monte Carlo study

Abstract: We show that a Heisenberg model of a spin cluster can describe subdomain ferromagnetic particles, from the dynamics of individual spins to the statistical behavior of the total magnetic moment of the cluster. While an analytical solution of the quantum spin problem is given for small clusters, a classical Heisenberg numerical simulation is used to study clusters of up to 561 atoms. We have studied magnetic behavior as a function of particle size, temperature, and magnetic field and find that the magnetization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This enhanced temperature dependence has also been reported in the gas phase experiment 17 and by Monte Carlo calculation. 18 To account for this effect, we introduced an empirical temperature dependent magnetic moment into the Langevin equation, namely m p m p0 e 2cT (c ranges from 0.010 to 0.020). The solid curves in Fig.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…This enhanced temperature dependence has also been reported in the gas phase experiment 17 and by Monte Carlo calculation. 18 To account for this effect, we introduced an empirical temperature dependent magnetic moment into the Langevin equation, namely m p m p0 e 2cT (c ranges from 0.010 to 0.020). The solid curves in Fig.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…A great deal of effort has been devoted to the theoretical and experimental study of transition metal (TM) clusters [7,8,9,10] which are known to have a relatively low anisotropy energy in the bulk compared to their exchange energy [2]. For TM clusters, it has been shown that it is the localised character of the 3d electrons at the surface which enhances the surface anisotropy with respect to the volume anisotropy [3].…”
Section: Introductionmentioning
confidence: 99%
“…A number of numerical simulations have been performed to study the magnetic properties of clusters or very small particles both at nonzero [1][2][3][4][5][6][7][8] and at zero temperatures. 9,10 The nonzero temperature properties have been studied in Monte Carlo (MC) simulations 1,2 assuming that the anisotropy of the particles can be neglected. While this assumption is reasonable when the particles are studied on an atomic level or when the magnetization of the particles behaves essentially paramagnetically, it excludes the low temperature properties when the magnetization shows hysteresis due to the anisotropy.…”
mentioning
confidence: 99%